Molecular Characterization of Potential Crop Pathogens Associated with Weeds as Endophytes in Uniilorin Plantations, Nigeria - A. A. Lateef; T. Garuba; K. A. Abdulkareem; B. U. Olayinka; G. S. Olahan; S. B. Adeyemi; K. A. Abdulkareem (مجلة بغداد للعلوم, 2022)
Crop diseases are usually caused by inoculum of pathogens which might exist on alternate hosts or weeds as endophytes. These endophytes, cum pathogens, usually confer some beneficial attributes to these weeds or alternate hosts from protection against herbivores, disease resistance, stress tolerance to secondary metabolites production. This study was therefore carried out to isolate potential crop pathogens which exist as endophytes on weed species in the University of Ilorin plantations. Green asymptomatic leaves were collected from 10 weed species across the plantations, and processed for their endophytic fungi isolation. Isolates were purified into pure cultures and used for molecular identification using the internal transcribed spacer (ITS) region of the ribosomal DNA. Phylogenetic analysis of the fungal sequences using MEGA software revealed 9 fungal genera belonging to 13 species, with species in the genera Curvularia, Epicoccum and Daldinia occurring in more than one weed species, while other genera such as Alternaria, Fusarium, Chaetomium, Macrophomina, Arthrinium and Phomopsis occurred in just one weed species each. Daldinia eschscholtzii was isolated in this study as an endophyte from Loudetia arundinacea for the first time. This plant is very abundant in Nigeria and Africa where it is used majorly for thatching and feeding livestocks. This also represents the first endophytic fungi from the genus Loudetia. Potential relationship between the occurrences of these fungi as endophytes and as pathogens are discussed. These discoveries represent the first large-scale molecular identification and several first reports of endophytes from these weed species. These results also represent the first records of some of these fungi in Nigeria.